Balancing Borders and Bridges: Negotiating the Work-Home Interface via Boundary Work Tactics - Kreiner, Glen E.; Hollensbe, Elaine C.; Sheep, Mathew L. (Academy of Management Journal, 2009)
We investigated how people manage boundaries to negotiate the demands between work and home life. We discovered and classified four types of boundary work tactics (behavioral, temporal, physical, and communicative) that individuals utilized to help create their ideal level and style of segmentation or integration. We also found important differences between the generalized state of work-home conflict and “boundary violations,” which we define as behaviors, events, or episodes that either breach or neglect the desired work-home boundary. We present a model based on two qualitative studies that demonstrates how boundary work tactics reduce the negative effects of work-home challenges.